A Review on Flame Retardants in Soils: Occurrence, Environmental Impact, Health Risks, Remediation Strategies, and Future Perspectives - Trang Le Thuy; Tuan-Dung Hoang; Van-Hiep Hoang; Minh-Ky Nguyen (Toxics)
As novel pollutants, flame retardants (FRs) are prone to accumulating in soil and might increase human health risks. It is advisable to emphasize the biomagnification of FRs within the terrestrial food chain, particularly concerning mammals occupying higher trophic levels. Exposure to soil particles laden with FRs may result in numerous health complications. These findings offer significant insights into FR pollutant profiles, tracing origins and recognizing health risks associated with soil samples. Reports have revealed that exposure to FRs can pose serious health risks, including neurodevelopmental impairments, endocrine system disruption, and an increased likelihood of cancer. Nanomaterials, with their high surface area and flexible properties, possess the ability to utilize light for catalytic reactions. This unique capability allows them to effectively degrade harmful contaminants, such as FRs, in soil. Additionally, biological degradation, driven by microorganisms, offers a sustainable method for breaking down these pollutants, providing an eco-friendly approach to soil remediation. These approaches, combined with optimum remediation strategies, hold great potential for effectively addressing soil contamination in the future. Further research should prioritize several key areas, including ecological behavior, contaminant monitoring, biological metabolomics, toxicity evaluation, and ecological impact assessment.